Music Bebasungan Implementation Of Pupuh Basung In The Selonding Gamelan | Karawitan Bebasungan Implementasi Pupuh Basung Dalam Gamelan Selonding - I Komang Alit Nova Adi Suastawan (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
Kidung is a literary work of poetry that has a specific meaning which is used in yadnya ceremonies for Hindus in Bali. One of the songs or pupuhs used is known as the Basung Pupuh. This pupuh is a ballad accompanied by gamelan xylophone during the Pitra Yadnya ceremony. Gratisungan's innovative work aims to apply kidung basung to the selonding gamelan so that in the future it will not only be used in pitra yadnya events but other yadnya ceremonies. The method used in this work is the Alma M. Hawkins method which consists of three parts, namely the exploration stage, the experimental stage improvisation, and the forming stage. The result of this work uses a structure in four parts, where each part has a different processing of musical elements to convey a sacred impression, with a concept designed based on the length and short length of the piece in each part so that it makes it easier for arrangers to explore and have aesthetic values.